2014
DOI: 10.1016/j.jvs.2014.03.267
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Coffee Consumption and Risk of Cardiovascular Disease: A Systematic Review and a Dose-Response Meta-Analysis of Prospective Cohort Studies

Abstract: Conclusions: Outcomes for repair of ruptured abdominal aortic aneurysms (rAAA) might be improved by wider use of local anesthesia for EVAR and by recognizing that a minimum blood pressure of 70 mmHg may be too low a threshold for permissive hypotension.Summary: Most data on outcomes of patients with rAAAs are singlecenter studies and as such may be too small to identify clinical factors that could improve overall patient outcomes. The IMPROVE study is a pragmatic multicenter randomized clinical trial in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
173
2
14

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(195 citation statements)
references
References 0 publications
6
173
2
14
Order By: Relevance
“…A single intake of coffee with a high content of chlorogenic acids and low content of hydroxyhydroquinone restored postprandial endothelial dysfunction by decreasing in oxidative stress. Epidemiologic studies have shown that coffee drinking is associated with lower risk of cardiovascular disease [15,[17][18][19]. In the present study, single intake of coffee with a high content of chlorogenic acids and low content of hydroxyhydroquinone, but not single intake of coffee with a high content of chlorogenic acids and high content of hydroxyhydroquinone or placebo coffee, significantly improved postprandial endothelial dysfunction.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…A single intake of coffee with a high content of chlorogenic acids and low content of hydroxyhydroquinone restored postprandial endothelial dysfunction by decreasing in oxidative stress. Epidemiologic studies have shown that coffee drinking is associated with lower risk of cardiovascular disease [15,[17][18][19]. In the present study, single intake of coffee with a high content of chlorogenic acids and low content of hydroxyhydroquinone, but not single intake of coffee with a high content of chlorogenic acids and high content of hydroxyhydroquinone or placebo coffee, significantly improved postprandial endothelial dysfunction.…”
Section: Discussionsupporting
confidence: 50%
“…In addition, the association between coffee drinking and risk of cardiovascular disease remains inconclusive [15,[17][18][19][20][21][22][23]. The reason for the controversial results remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consumption of Indian spices need to be carefully controlled to avoid induction of obesity by complete nulli ication of caffeine's co-ordination of the neuroendocrine system by dysregulation of the brain, adipose tissue and liver interaction. Caffeine and its metabolism is critical to cardiovascular disease [50][51][52] with Indian spice intake (mg/day) now important with relevance to interference with caffeine's therapeutic properties in man and various species. Delayed caffeine clearance leads to interference with caffeine's bene icial effect on adipogenesis with increased transport to the brain relevant to mitochondrial induced apoptosis and the induction of Type 3 diabetes [26][27][28].…”
Section: Editorialmentioning
confidence: 99%